Analysis of The Financial Performance of Islamic Commercial Banks Using The Sharia Conformity Method and Profitability Method - Janah, Mirta Ulfah Rufi Widya; Muharammi, Rais Sani (Journal of Business and Management Review, 2023)
It takes a measuring tool that has been adjusted to the concept and practice of Islamic banking a measurement tool that has been adapted to the concept and practice of Islamic banking, namely by assessing the sharia complience side of Islamic banking without ignoring the profitability side. So that the Sharia Conformity and Profitability (SCnP) Model needed. The purpose of this study is to analyze the financial performance of commercial banks using SCnP in 2017-2021. The method used is descriptive quantitative with the data source of the Annual Report of Islamic Commercial Banks downloaded from the official website of each bank. The population in this study were all BUS financial reports registered in OJK. The sampling technique used is purposive sampling with criteria that Islamic commercial banks has the highest level of profitability in 2021 (6 most). The result of this study indicate that measuring the financial performance of Islamic commercial banks using the Sharia Conformity and Profitability (SCnP) method at Islamic commercial banks in Indonesia from 2017 to 2021 shows different result. 2017, 2020, and 2021 are spread across for quadrants. While in 2018 to 2019 it was spread in three quadrants, namlely Upper Left Quadrant (ULQ), Lower Right Quadrant (LRQ), and Lower Left Quadrant (LLQ).